What Happened to Asian Exports During the Crisis? - Spilimbergo, Antonio (International Monetary Fund, 2000)
After the large exchange rate depreciations following the 1997 East Asian crisis, export volumes from East Asian countries responded with a notable lag. Two main explanations for this lag have been proposed: that the policy of high interest rates limited access to domestic credit and hence limited the supply of exports; and that "competitive depreciation" neutralized the effects on demand for exports. This paper considers the plausibility of these two mechanisms using a new monthly database on exports of selected industries. We find evidence that "competitive depreciation" did play a fundamental role in the propagation of the East Asian crisis through the trade channel, even at a monthly frequency